Short enantioselective synthesis of the antiepileptic agent, levetiracetam based on proline-catalyzed asymmetric alpha-aminooxylation - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of a new antiepileptic drug, levetiracetam is described, in high optical purity (> 99.5% ee), using proline-catalyzed alpha-aminooxylation of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.

Short synthesis of (+)-harzialactone A and (R)-(+)-4-hexanolide via proline-catalyzed sequential alpha-aminooxylation and horner-wadsworth-emmons olefination of aldehydes - Kotkar, Shriram P.; Suryavanshi, Gurunath S.; Sudalai, Arumugarn (Tetrahedron-Asymmetry, 2007)
{In melts, ring polymers assume more compact conformations compared to linear chains with the same degree of polymerization N-r, i.e. R-r similar to N-r(nu) with nu approximate to 0.4, where R-r is the radius of gyration. Upon gradually substituting some of the ring polymers with linear chains, the ring molecules swell. In the limit of infinite dilution, their size scales as R-r similar to N-r(0.5). We present a scaling argument based on the blob model to capture this transition. Ring-linear blends are modeled as a semidilute solution of ring polymers in a theta-solvent consisting of linear chains. The model predicts that the size of the ring polymer remains unchanged up to the overlap concentration c(r)(*
Keywords: core-shell nanoparticles; Gold; HRTEM; interfacial seeded growth; Silver; XPS